Enhancing the knowledge level of dog owners using an electronic self-learning module - RUPASI TIWARI; MUKESH KUMAR; B P SINGH; D E UJJWAL; SUNIL KR JHA; TRIVENI DUTT (Indian Journal of Animal Sciences, 2016)
The present study was taken up to assess the knowledge about dog health and management among the pet owners and the effectiveness of a need based electronic self learning module “Dog Health Management Trainer” (DHMT) for enhancing their knowledge. The DHMT was developed and tested on 100 dog owners visiting the polyclinic at IVRI. Results revealed that dog owners were mainly facing problems related to diseases of skin, gastrointestinal system and parvoviral infection besides various other problems. Majority of the owners had medium knowledge about dog diseases while low knowledge about dog breeding and reproduction. Results revealed that DHMT was highly effective in enhancing the knowledge level and dog owners found it very much interesting and user friendly with an overall utility index of 0.87. The price proposed was negatively and significantly correlated with the pre-test knowledge scores for dog health indicating that those dog owners who were having low knowledge quoted higher price for procuring the DHMT.